Intuisi Siswa SMK dalam Memecahkan Masalah Matematika Ditinjau dari Kemampuan Matematika dan Perbedaan Gender - Nazariah Nazariah; marwan marwan; Zainal Abidin (Didaktik Matematika, 2017)
Mathematics learning activities would not be separated from the problem of mathematics. The mathematical will be a problems if in solving problem students does not immediately know the answer, but it takes time to think what steps should be taken to resolve the issue. In fact, many students are good at solving mathematical problems often use smart ways beyond of expectations and habits, thereby providing a short and accurate answer. in contrast to the students who have moderate or low mathematical ability, the way that used to solve the problem tend to give answers lengthy and sometimes less accurate, although many low of students math skills who have difficulties to find a way to solve mathematical problems. It showed that, there is a correlation between mathematical abilities of the students with intuition that students use in solving mathematical problems. On the other hand, the gender factor influencing the way to gain knowledge of mathematics. The influence of the gender factor in the process of conceptualization showed that gender may affect the use of intuition in understanding mathematical concepts. The aims of this study is to determine the differences between women's and mens intuition on vocational students who have a high level of mathematical ability, medium and low in mathematical problem solving. This study used a qualitative approach with descriptive research without the use of statistical analysis. the population is a whole class X SMK 1 Banda Aceh by taking six subjects consisted of 3 male and 3 female subjects at various levels, through learning achievement tests and consultation with subject teachers. Data collected by using a test instrument covering mathematical problem solving ability test and an interview. Based on this research, note that: 1) The differences characteristic between women and men on the subjects intuition in solving mathematical problems by using solving Polya; 2) the differences intuition subjects between men and and women in solving mathematical problems by solving Polya; 3) There are differences intuition on various materials.